Exploring political and gender relations : new digital and cultural environments - Marinescu, Valentina; Branea, Silvia (Cambridge Scholars Publishing, 2017)
The present volume offers a contemporary, multicultural approach to the controversial relationship between politics, media and society. The contributors here analyse such links from a variety of different perspectives, and represent perspectives from various countries across Europe, Asia, North America and South America. Despite their geographical diversity, they manage to reach a common language in their studies, offering a re-positioning of the study of media, society and politics. The new perspectives offered by this volume will be of interest to any media studies scholar, because they brin.